Optic nerve head drusen in children – visual function and OCT outcomes - Chrzanowska, Beata; Szumiński, Michał; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Purpose: To evaluate the effect of optic nerve head drusen on retinal nerve fiber layer (RNFL) thickness In children, with the use of optical coherence tomography (OCT). Material and methods: 21 patients (mean age 13.9 years) with optic nerve head drusen were studied prospectively. For statistic comparison a group of 15 control subjects (mean age 14.1 years) participated. Ophthalmologic examination, automated visual field testing and optical coherence tomography were performed in each patient. For statistical analysis we used Shapiro-Wilk and U Mann-Whitney tests. Results: In the OCT measurements the nasal RNFL was significantly thinner as compared to the reference group. Neither statistically significant thinning of global RNFL between groups nor relation between subjects age and RNFL thickness was found. Conclusions: Optic nerve head drusen can lead to visual function defects, therefore early and correct diagnosis is mandatory. Optical coherence tomography is a usefull diagnostic tool used to determine the cause of disc elevation, which is especially important in childhood, when drusen can cause disc to appear papilledema-like. Overall OCT appears to be a non-invasive, sensitive and early-indicating method of RNFL thinning.